The Business of Software: The Goldilocks Estimate. - Armour, Phillip G. (Communications of the ACM, 2012)
The author discusses project estimates in software development, arguing that organizations often make decisions based on low quality estimates made quickly with little research or spend too much time and money accounting for any possible uncertainty in a project estimate. He outlines a formula for the calculation of an estimate which optimizes time and cost on the basis of project goal target cost and the parameter of the business practice supported by the project.